Multiple Chronic Conditions in Spousal Caregivers of Older Adults With Functional Disability: Associations With Caregiving Difficulties and Gains. (18th September 2017) - Polenick, Courtney A; Leggett, Amanda N; Webster, Noah J; Han, Benjamin H; Zarit, Steven H; Piette, John D
Abstract: Objectives: Multiple chronic conditions (MCCs) are common and have harmful consequences in later life. Along with managing their own health, many aging adults care for an impaired partner. Spousal caregiving may be more stressful when caregivers have MCCs, particularly those involving complex management. Yet, little is known about combinations of conditions that are most consequential for caregiving outcomes. Method: Using a U.S. sample of 359 spousal caregivers and care recipients from the 2011 National Aging Trends Study and National Study of Caregiving, we examined three categories of MCCs based on similarity of management strategies (concordant only, discordant only, and both concordant and discordant) and their associations with caregiving difficulties and gains. We also considered gender differences. Results: Relative to caregivers without MCCs, caregivers with discordant MCCs reported fewer gains, whereas caregivers with both concordant and discordant MCCs reported greater emotional and physical difficulties. Wives with discordant MCCs only reported a trend for greater physical difficulties. Caregivers with concordant MCCs did not report more difficulties or gains. Discussion: Spousal caregivers with MCCs involving discordant management strategies appear to be at risk for adverse care-related outcomes and may benefit from support in maintaining their own health as well as their caregiving responsibilities.